Environmental Social Governance : Pengaruhnya Terhadap Perpajakan dan Return Saham dengan Return on Capital Employed Sebagai Pemoderasi - Lestari, Putri Gantine; Meila, Kaca Dian; Himmah, Elok Faiqoh (Economics Professional in Action (E-Profit), 2024)
Currently the world were facing a multidimensional crisis known as "Perfect Storm". The crisis being faced is not only Covid-19 which has had a significant impact on various sectors except the social, environmental and economic crises. The issue of climate change due to the effects of carbon use which is thought to originate from company activities is one of the contributors to pollution in various countries. Therefore, currently companies need to align company activities with concepts related to the environment, social and governance. Environmental, Social, Governance (ESG) is a company standard where every company activity must comply with ESG achievement indicators. Mining companies are companies whose operational activities are directly related to nature, so mining companies are expected to have good ESG. This research aims to examine the influence of ESG on Taxation and Stock Returns and whether Return on Capital Employed as an indicator of Economic Performance can moderate the influence of ESG on taxation and Stock Returns. The unit of analysis in this research is mining sector companies listed on the Indonesia Stock Exchange in the 2019-2022 period. The data collection method in this research is using a purposive sampling method. Based on the research results, it was found that (1) ESG has a negative effect on taxation as proxied by ETR. (2) Retun On Capital Employed can moderate the influence of ESG on Taxation. (3) ESG has a positive effect on stock returns. (4) Return On Capital Employed can moderate the influence of ESG on Stock Returns.